Problem Solving For Fifth Grade In Quadrilateral Learning Using Van Hiele Theory And Contextual Approach - Debora Dwi Kurniawati; Savira Erdia Kusuma; Yulisa Ananda Putri; Haniek Sri Pratini (Universitas PGRI Yogyakarta, 2022)
This research is a literature study with a qualitative approach. This research is motivated by the importance of students' understanding of the material properties of quadrilaterals. The purpose of this study is that researchers want to find out whether Van Hiele's theory and contextual approaches are effective in increasing the understanding of fifth grade elementary school students about the material properties of quadrilaterals. Van Hiele's theory is a theory that is specifically used in the field of geometry which has 5 stages of learning, namely the information stage, the directed orientation stage, the explicitization stage, the free orientation stage, and the integration stage. While the contextual approach emphasizes on 7 contextual components, namely: (1) Constructivism, (2) Asking, (3) Finding, (4) Learning Society, (5) Modeling, (6) Reflection, (7) Actual assessment. So that learning is obtained through knowledge and experience or the real world, improving students' higher order thinking processes, student-centered, active students, critical, creative, problem solving, students learn in a fun, exciting, not boring, and use various learning resources. The results of this study indicate that there is an increase in students' understanding of the material properties of quadrilaterals by using Van Hiele's learning theory and contextual approach.